Growth dynamics and morphological components in mexican plum fruits (Spondias purpurea L.) - Maldonado Peralta, María de los Ángeles; Rojas-García, Adelaido Rafael; Aguirre, Herminio Aniano; Ramírez-Reynoso, Omar; Palemón-Alberto, Francisco; Maldonado Peralta, Ramiro (Ecosistemas y Recursos Agropecuarios, 2025)
The conservation of genetic resources in their center of origin makes it possible to meet nutritional needs in future times. With the objective of evaluating the growth dynamics and morphological components in mexican plum fruits (Spondias purpurea L.) collected on the Costa Chica of Guerrero and Oaxaca. 95 trees were identified. For the growth curve, 50 recently tied fruits were labeled. For morphological quality, ripe fruits were harvested; four repetitions of 100 fruits were taken at random. Weight, polar and equatorial diameter, shape and color were evaluated in fruits and seeds. The data were analyzed using measures of central tendency (SAS® 9.3). Mexican plum fruits reach maturity in 79 days. The growth curve presented a dynamic that corresponds to the double sigmoidal type. Nine accessions were found. The heaviest fruits were those of accessions 1, 3, 7 and 9, they are oval in shape. The seeds are woody and fibrous, weighing from 1.47 to 3.30 g, elongated in shape. The majority presented 80.00% or more of the edible part. The fruits presented commercial quality, but some are acidic for fresh consumption, complementary research is recommended to address aspects related to added value.